The Effect of Problem-based Learning Model and Peer Tutor Method Application on Comprehension of Musical Notation Reading for Grade VII Students of SMP Negeri 1 Menes (Catharsis, 2022)
Musical notation is a music writing system in the form of images. Musical notation has become material in the learning syllabus, but, unfortunately, it cannot be conveyed optimally to the students. Based on the explanation above, the researchers have made the problems students experienced the main foundation of the learning process. It is supported by using the PBL model. In order to maximize the results of the PBL model combined with the Peer Tutor method, the use of this method makes the students the centre of learning. The combination of the PBL model and the Peer Tutor method aims to test if its application significantly affects the students' comprehension of musical notation reading. The research method used was quantitative with a quasi-experimental approach. The sampling technique used purposive samples, and the hypothesis testing employed the paired t-test formula. The results of this study are in the form of answers to the hypothesis, which are supported by the statistical test results. There is a significant difference in the average post-test score between the experimental and control groups. Based on the data, the tcount value is 13.777, while the ttable value is 1.67, with df = 58 and the significance level = 0.05. It is clear that tcount>t table, so Ho is rejected, meaning there is an average difference between the post-test and pre-test scores.